IMPLEMENTASI PROGRAM KEAGAMAAN UNTUK PENGUATAN KARAKTER RELIGIUS SISWA DI SDN MRICAN 2 KOTA KEDIRI - Rahmad Triyuda; Alfi Laila; Dini Nur Faticha Sari; Lutfia Wahyuningtyas (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
Religious character education at the elementary school level plays a strategic role in shaping students’ moral, spiritual, and prosocial attitudes. Social change and the development of digital technology often weaken the habituation of worship, discipline, and exemplary behavior. Therefore, schools need to implement structured and inclusive religious programs based on daily habituation. This study aims to examine how the religious programs are implemented, the impacts of these programs, and the challenges encountered in strengthening religious character at SDN Mrican 2. This research employed a descriptive qualitative approach using observation, interviews with the principal, Islamic education teachers, and students, as well as documentation of the programs. Data validity was strengthened through source and technique triangulation, while data analysis followed the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The findings show that religious programs are routinely carried out through Congregational Dhuha Prayer, istighosah–tahlil, Friday Worship, Friday Sharing, MTQ activities, and calligraphy for Muslim students. Christian students participate in morning prayer, worship, and thanksgiving services guided by religious teachers. These habituation activities have formed an inclusive religious culture. Positive impacts are evident in students’ increased discipline, responsibility, social awareness, cooperation skills, and tolerance for diversity. Challenges encountered include inconsistency in students’ discipline, differences in understanding worship activities, limited facilities, and suboptimal involvement of non–Islamic education teachers. Overall, the habituation-based religious programs are proven effective in shaping religious and social character. To optimize the outcomes, continuous evaluation, strengthened teacher involvement, and innovation in habituation strategies are needed. ABSTRAK Pendidikan karakter religius pada jenjang sekolah dasar memiliki peran strategis dalam membentuk moral, spiritual, dan sikap prososial peserta didik. Perubahan sosial serta perkembangan teknologi digital sering melemahkan pembiasaan ibadah, disiplin, dan keteladanan. Oleh karena itu, sekolah perlu menerapkan program keagamaan berbasis pembiasaan yang terstruktur dan inklusif. Penelitian ini bertujuan mengetahui bagaimana pelaksanaan program keagamaan, dampak pelaksanaan program keagamaan, serta tantangan yang dihadapi dalam melaksanakan program keagamaan untuk penguatan karakter religius di SDN Mrican 2. Pendekatan penelitian menggunakan kualitatif deskriptif dengan teknik observasi, wawancara terhadap kepala sekolah, guru Pendidikan Agama Islam, serta peserta didik, dan dokumentasi program. Validitas data diperkuat melalui triangulasi sumber dan teknik, sedangkan analisis menggunakan model Miles dan Huberman melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa program keagamaan dilaksanakan secara rutin melalui Salat Dhuha Berjamaah, istighosah–tahlil, Jumat Ibadah, Jumat Berbagi, MTQ, dan kaligrafi untuk siswa Muslim. Siswa Nasrani mengikuti doa pagi, ibadah, dan layanan syukur yang dipandu guru agama. Pembiasaan ini membentuk budaya religius yang inklusif. Dampak positif terlihat pada meningkatnya kedisiplinan, tanggung jawab, kepedulian sosial, kemampuan bekerja sama, dan toleransi keberagaman. Kendala yang dihadapi meliputi ketidakkonsistenan disiplin siswa, perbedaan pemahaman terhadap kegiatan ibadah, keterbatasan fasilitas, serta keterlibatan guru non-PAI yang belum optimal. Secara keseluruhan, program keagamaan berbasis pembiasaan terbukti efektif membentuk karakter religius dan sosial. Agar lebih optimal, diperlukan evaluasi berkelanjutan, penguatan peran seluruh guru, dan inovasi strategi pembiasaan.